Effects of some sesquiterpenes on the stored-product insect Tenebrio molitor L. (Coleoptera: Tenebrionidae) - Garcia, Matias (2003)
In order to evaluate the allelochemical activity of some sesquiterpenes isolated from the native plant Tessaria absinthioides (Hook. et Arn.) DC, and some semi synthetic derivatives against Tenebrio molitor L. larvae, we have developed bioassays directed to quantify repellency, larval mortality, and its effects on the development. Although costic aldehyde caused the maximum repellent effect, all the compounds showed a significant effect at some dose or time, indicating behavioral avoidance. The topical application of costic aldehyde produced the largest increase on the duration of the pupal stage. Tessaric acid exhibited the highest toxicity by topical application at the experiment closure. Both eremophilane–1(10),2,11(13)–triene–12–oic, and g-costic acids induced some morphological deformities.